Patent Law and Its Enforcement in Indonesia, Japan and the USA - Purwaningsih, Endang (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2020)
The fundamental issues in the era of industrialization is the protection of patent rights and the enforcement of the patent law. In Indonesia, Intellectual Property Rights (IPR) including patent tend to be violated with regard to foreign investment and transfer of technology issue. Therefore, as a member of the WTO, it is necessary for Indonesia to learn fromÂ other countries such as Japan and the United States of America, especially in terms of regulations. The purpose of this study is to find out the fundamental differences among Indonesia, Japan and America regarding the protection of patent rights and the enforcement of patent law. This research is a normative legal research. Data is collected from books, international journals, relevant laws and government regulations. The results show that the scope of patent protection in Japan, the United States and Indonesia has so far followed TRIPs and WTO provisions. Basically, Indonesia, Japan, and America have the same acquisition system, namely â€œfirst to fileâ€. Historically before 2013 America has ever used â€œfirst to inventâ€ system. Coverage of protection remains the same in the fields of technology and industry, but Japan extends the scope of patents to cover those produced by the employees and Indonesia also adopts thisÂ model. In term of enforcement, Indonesian patent law also develops Â a new appeal commission to settle patent disputes.